THE CHALLENGES OF SECURITY THREAT IN NIGERIA CYBERSPACE - Saidu, I. R.; Suleiman, T.; Akpan, U. E. (FUDMA JOURNAL OF SCIENCES, 2021)
This research work was conducted to examine critically and systematically cyber threat intelligence challenges and prospects in Nigeria. It judges the value and relevance of cyber threat intelligence in the society where they are lacking in providing necessary information. Dealing with these challenges that may cause threat intelligence to be useless has become a major concern to Nigeria. The work was intended to achieve the following objectives: to examine the nature of cybersecurity in Nigeria, to analyse the cybersecurity threats that can disrupt the functioning of the country, to identify the challenges facing the Nigeria cyberspace and the conduct of a cyber threat intelligence analysis, to discuss the means by which cyber threat can be used to boost Nigeria’s National Security Policy, to make recommendations to preserve important intelligence capabilities while ensuring the protection of its critical infrastructures through the use of threat intelligence. The scope of the study was limited to the period 2009 – 2019. The research was analytical. Relevant data were collected from both primary and secondary sources of data. The data analysis used the percentage instrument and the following conclusions were drawn: that threat data overload, threat data quality, privacy and legal issues and interoperability issues are some of the challenges of cyber threat intelligence; also, the need to continually invest in research, build local cyber threat management infrastructure and enhance the ability to anticipate, detect, respond and contain information security threats is very crucial. Nigeria
Keywords: cyberspace, cybersecurity, cyberthreat, threat intelligence, data overload and privacy